Petrografia, química mineral e geotermobarometria de metapelito do grupo carrancas na Nappe de Luminárias (MG) - Fumes, Regiane Andrade [UNESP]; Luvizotto, George Luiz [UNESP]; Moraes, Renato; Ferraz, Edson Ricardo Maia [UNESP] (My University, 2017)
The Luminárias Nappe is a NNE-SSW elongated structure, located in the southern portion of the Neoproterozoic Brasília Orogen, which borders the São Francisco Craton, MG, Brazil. It is composed of metapelite and quartzite from the Carrancas Group. The present work focuses on the metamorphic characterization of the Luminárias Nappe by means of petrography, mineral chemistry and average PT method of THERMOCALC. In the northern portion, the paragenesis is Chl+St+Ky+Rt+Qtz+Ms; in the center-north it is St+Grt+Bt+Rt+Qtz+Ms and in the southern it is Grt+Ky+St+Rt+Qtz+Ms. Retrometamorphic chlorite is observed in the center-north and southern portions, while retrometamorphic biotite is observed in the southern portion. Mineral chemistry data on the rock forming minerals show differences in the composition of minerals from the northern, center-north and southern portion of the Luminárias Nappe. Metamorphic peak conditions (average PT) in the center-northern portion are 570 ±67 ˚C and 9.4 ±1.9 kbar, in the southern portion are 609 ±63 ˚C and 11.4 ±3.9 kbar. Results indicate the presence of a metamorphic gradient with conditions increasing from lower amphibolite facies in the northern and center-north to medium amphibolite in the southern portion, both at high-pressures.
Petrography, mineral chemistry and thermobarometry of metapelite of the carrancas group in the LuminÁrias Nappe – Minas Gerais – Brazil
Keywords: Average PT; Carrancas group; High-pressure amphibolite facies; Mineral chemistry; THERMOCALC